MENDENGAR SEBAGAI SALAH SATU ALAT KOMUNIKASI - Dewi, Yuni Retna (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
Surveys indicate  managerial  people  in organizations  spend up to 80 percent  of their workday in toceto   face  conversations,  in meetings,  on the phone,  or writing,  other research has suggested that approximately  60  percent   of  the workday to spent  listening, yet   the   estimates   are   that   less  than  50  percent    of  the   area messaged used in a day are fully understood. A  recent   survey  of  Australia   business executives   showed that  the ability to listen was ranks as the most important communications  skill necessary  for persona/- success in  the organizations. Similar  results   were    obtained   in   a    1982.   Study     after communication  skills Australian  accounting raduates. The purpose  of this writing  is  to increase awareness  of how much  of our day  was  spent listening,  to identify  some  of the major barriers   of   effective   listening,   and    finally    to   learn    how    to concentration,    objectivity,    questioning   and     feedback    can improve  listening behavior. Listening   is    the   communication   channel    we    use  most frequently.  Yet  surveys  show   that   listening   skills are   the   least developed !.